2023
DOI: 10.3390/clockssleep5020014
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Sleep Quality of Physical Exercise Programs in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Background: Given the beneficial effects of exercise in different populations and the close relationship between healthy ageing and sleep quality, our objective was to determine if physical exercise delivered through a structured program improves sleep quality in older adults. Methods: Embase, PubMed/MEDLINE, Web of Science, and Cochrane Register of Clinical Trials (CENTRAL) were searched to 15 January 2023. Studies that applied physical exercise programs in older adults were reviewed. Two independent reviewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Compared to non-smokers, smokers have shorter sleep duration, longer sleep onset latency, and a higher likelihood of developing sleep apnea [ 41 ]. Previous research has demonstrated that physical activity can serve as an effective non-pharmacological intervention to improve sleep quality [ 42 ]. Findings from a randomized clinical trial indicated that tai chi or regular physical activity significantly enhanced objective sleep efficiency and decreased the duration and frequency of awakenings after sleep onset in patients with insomnia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to non-smokers, smokers have shorter sleep duration, longer sleep onset latency, and a higher likelihood of developing sleep apnea [ 41 ]. Previous research has demonstrated that physical activity can serve as an effective non-pharmacological intervention to improve sleep quality [ 42 ]. Findings from a randomized clinical trial indicated that tai chi or regular physical activity significantly enhanced objective sleep efficiency and decreased the duration and frequency of awakenings after sleep onset in patients with insomnia [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise has long been proven to effectively improve sleep quality. 46 Exercise increases the body’s oxygen consumption and affects the secretion of metabolic products such as inorganic phosphates, regulating individual’s sleep quality. 47 Exercise is beneficial for the structure and function of the brain, especially in the elderly, and the improvement of sleep quality through exercise is the foundation for improving cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as individuals age, notable changes occur in sleep patterns, including alterations in sleep quality and quantity, such as slow-wave sleep, spindle density, and sleep continuity ( 49 ). However, the existing literature on interventions to enhance sleep in older adults remains limited, with exercise being the primary consideration for potential improvement in sleep quality for this population ( 50 ). Similarly, maintaining adequate nutrition has been shown to improve the sleep quality of older adults ( 51 ).…”
Section: Discussionmentioning
confidence: 99%